2011
DOI: 10.1016/j.transproceed.2011.08.114
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Ischemia/Reperfusion Injury and the Stimulus of Fibrogenesis in an Experimental Model: Comparison Among Different Preservation Solutions

Abstract: In this experimental model of early reperfusion injury, preservation changes related to higher levels of renin, which suggest its role in fibrogenesis. FBP was associated with lower renin levels than other solutions including UW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…The same bloodlike fluid was used for 2 hours of ex vivo reperfusion of all rat livers, and the same perfusion system was used for NMP and ex vivo reperfusion. Previous studies have indicated that crystalloid fluids are sufficient for short‐term cold preservation of rat donor liver parenchyma . In a pilot study, we confirmed that rat donor liver preservation in either NaCl or histidine tryptophan ketoglutarate (HTK) solution (n = 6 in each group) does not result in a different degree of bile duct injury or function as measured by bilirubin, gamma‐glutamyltransferase (GGT), lactate dehydrogenase (LDH), pH, and HCO 3 − in bile produced during reperfusion (Supporting Text).…”
Section: Methodssupporting
confidence: 71%
See 2 more Smart Citations
“…The same bloodlike fluid was used for 2 hours of ex vivo reperfusion of all rat livers, and the same perfusion system was used for NMP and ex vivo reperfusion. Previous studies have indicated that crystalloid fluids are sufficient for short‐term cold preservation of rat donor liver parenchyma . In a pilot study, we confirmed that rat donor liver preservation in either NaCl or histidine tryptophan ketoglutarate (HTK) solution (n = 6 in each group) does not result in a different degree of bile duct injury or function as measured by bilirubin, gamma‐glutamyltransferase (GGT), lactate dehydrogenase (LDH), pH, and HCO 3 − in bile produced during reperfusion (Supporting Text).…”
Section: Methodssupporting
confidence: 71%
“…Previous studies have indicated that crystalloid fluids are sufficient for short-term cold preservation of rat donor liver parenchyma. (17,18) In a pilot study, we confirmed that rat donor liver preservation in either NaCl or histidine tryptophan ketoglutarate (HTK) solution (n 5 6 in each group) does not result in a different degree of bile duct injury or function as measured by bilirubin, gamma-glutamyltransferase (GGT), lactate dehydrogenase (LDH), pH, and HCO 3 2 in bile produced during reperfusion (Supporting Text). For both NMP and ex vivo reperfusion of rat donor livers, we developed a liver machine perfusion system that enabled dual perfusion via both the hepatic artery and the portal vein in a closed circuit ( Fig.…”
Section: Scs and Nmpmentioning
confidence: 59%
See 1 more Smart Citation
“…In our study, the "n = 9" was statistics by power analyses from preliminary experiment that used 2 groups of mean comparison sample cases formula. 32 From a statistical point of view, this sample was powered enough for pairwise comparisons of these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…These procedures use various preservation materials, solutions, and/or chemicals to ensure that the entire organ remains viable and can resume its physiological functions after transplantation into the recipient’s body. However, the effects of the different types of solutions used for preservation/transportation on the cells and their influence on clinical efficacy in patients needs further extensive research 37,38. Preserving an organ which is a conglomeration of many different tissue types consisting of billions of cells, employing varied materials and methodologies of preservation for more than few hours is acceptable with limited or no studies of randomized trials on safety and efficacy.…”
Section: Discussionmentioning
confidence: 99%